Embodied Predictions, Agency, and Psychosis - Leptourgos, Pantelis; Corlett, Philip R. (Frontiers in Big Data, 2020)
Psychotic symptoms, i.e. hallucinations and delusions, involve gross departures from conscious apprehension of consensual reality; respectively perceiving and believing things that, according to same culture peers, do not obtain. In schizophrenia, those experiences are often related to abnormal sense of control over one’s own actions, often expressed as a distorted sense of agency (i.e. passivity symptoms). Cognitive and computational neuroscience have furnished an account of these experiences and beliefs in terms of the brain’s generative model of the world, which underwrites inferences to the best explanation of current and future states, in order to behave adaptively. Inference then involves a reliability-based trade off of predictions and prediction errors, and psychotic symptoms may arise as departures from this inference process, either an over- or under-weighting of priors relative to prediction errors. Surprisingly, there is empirical evidence in favour of both positions. Relatedly, there is evidence for both an enhanced and a diminished sense of agency in schizophrenia. How can this be? We argue that there is more than one generative model in the brain, and that ego- and allo-centric models operate in tandem. In brief, ego-centric models implement corollary discharge signals that cancel out the effects of self-generated actions while allo-centric models compare several hypothesis regarding the causes of sensory inputs (including the self among the potential causes). The two parallel hierarchies give rise to different levels of agency, with ego-centric models subserving “feelings of agency” and allo-centric predictions giving rise to “judgements of agency”. Those two components are weighted according to their reliability and combined, generating a higher-level “sense of agency”. We suggest that in schizophrenia a failure of corollary discharges to suppress self-generated inputs results in the absence of a “feeling of agency” and in a compensatory enhancement of allo-centric priors, which might underlie hallucinations, delusions of control but also, under certain circumstances, the enhancement of “judgments of agency”. We discuss the consequences of such a model, and potential courses of action that could lead to its falsification.